(untitled) (Global Journal of Medical Research, 2023)
SARS-COV-2 is a virus that has led to the death of a large number of persons and caused a global endemic problem since December 2019 Vaccines have been prepared and authorized in an argent way to survive lives Any possible or known tactic has been used to prevent its spreading treat infected individual and to understand how it changes its structure to produce in advance a pre-made vaccine that could be used in an adequate time Understanding their antigenIcity mutation adaptation different types of the produced vaccines its in cito interaction and the like are essential to win the battle Humanity has been winning the battle against some more virulence viruses like smallpox human virus and the Rinderpest animal virus using strategies that could only describe nowadays as a simple method This review is concerned with highlighting important issues concerning SARS-COV-2 and its vaccine s structure epitopes RNA surface antigens personalizing the individual different responses the need for case-by-case treatments and the like